Validity and reliability of self-reported weight, height and body mass index from telephone interviews Validade e confiabilidade do peso, estatura e índice de massa corporal auto-referidos obtidos por entrevista telefônica - Alessandra Lucca; Erly Catarina Moura (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
The objective of this study was to examine factors associated with the validity of self-reported anthropometric measures. The authors selected 726 adults, aged 40 or older, living in the greater metropolitan region of São Paulo, Brazil. Self-reported weights and heights obtained from telephone interviews were compared to values measured directly by means of a multicenter survey. Mean differences (±SD) between self-reported and measured weights and heights among men were 0.54 (±0.30kg) and 1.98 (±0.31cm); while among women, they were -0.48 (±0.23kg) and 3.97 (±0.28cm), respectively. Sensitivity and specificity to diagnose obesity were 71% and 98% for males, and 78% and 96%, for females, respectively. There was good agreement between measured and self-reported weights and body mass index (BMI) among both sexes, however, self-reported height was less reliable. Self-reported weight and height obtained from telephone interviews are valid to estimate the obesity prevalence in this population, although systematic bias was found. Thus, it is desirable that researchers develop their own equations depending on the population being studied. O objetivo deste estudo foi investigar os fatores associados com a validade das medidas antropométricas auto-referidas. Estudaram-se 726 adultos, com 40 anos ou mais, residentes na área metropolitana de São Paulo, Brasil. A diferença média (±DP) entre peso e estatura auto-referidos e aferidos entre homens foi 0,54 (±0,30kg) e 1,98 (±0,31cm), respectivamente; enquanto entre mulheres foi de -0,48 (±0,23kg) e 3,97 (±0,28cm), respectivamente. A sensibilidade e especificidade no diagnóstico da obesidade foram 71% e 98% entre homens, e 78% e 96%, para mulheres, respectivamente. O peso referido e o índice de massa corporal (IMC) calculados com base no peso e na altura referidos apresentaram boa concordância quando comparadas às suas respectivas aferições. A estatura auto-referida, no entanto, mostrou-se menos confiável. A obtenção da informação do peso e estatura por entrevista telefônica é um método válido para estimar a prevalência da obesidade nesta população, apesar dos vieses sistemáticos encontrados. Aconselha-se que os pesquisadores desenvolvam suas próprias equações baseadas na população a ser estudada.